2017
DOI: 10.1016/j.cogdev.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Neurodynamic correlates of response inhibition from emerging to mid adulthood

Abstract: Response inhibition, a key executive function, continues to develop in early adulthood in parallel with maturational processes of the underlying prefrontal regions known to support it. The current study examined behavioral and neurophysiological correlates of response inhibition during a visual Go/No-Go task in a large sample (N = 120) comprised of participants in their Early 20s (ages 19–21), Mid 20s (ages 23–27), and Early 30s (ages 28–42). The two younger groups had lower accuracy, shorter reaction times, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 65 publications
0
19
0
1
Order By: Relevance
“…2 KNEŽEVIĆ response inhibition is presented in a companion article (Knežević & Marinković, 2017). Hajcak (2009a, 2009b) investigated how the number of error trials would influence the quantification of error-related brain activity (ERN and Pe) and found that the ERN and Pe became stable when eight trials were included.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 KNEŽEVIĆ response inhibition is presented in a companion article (Knežević & Marinković, 2017). Hajcak (2009a, 2009b) investigated how the number of error trials would influence the quantification of error-related brain activity (ERN and Pe) and found that the ERN and Pe became stable when eight trials were included.…”
Section: Participantsmentioning
confidence: 99%
“…In our previous study (Knežević et al, 2016), we found age-related differences in the neural basis of performance monitoring between young adults aged 18–19 and young adults aged 23–25. Given that studies showed protracted brain development up to the age of 28, in order to acquire a complete picture of response inhibition advancement throughout young adulthood, in the following study, we included a group of young adults aged above 28 years (Knežević & Marinković, 2017) since at this life stage, we do not expect significant brain maturational changes (Knežević, 2018). Indeed, we found that on the behavioral level, those in their early 20s and mid 20s showed more impulsive responses compared to participants in their early 30s.…”
mentioning
confidence: 99%
“…The recent studies point to new vulnerabilities in EA that predispose people to various neurological and psychological problems (Taber-Thomas & Perez-Edgar, 2016). Brain studies using data collected with fMRI machines conducted in recent years have found a neurological basis for EAs’ lack of impulse control (Knežević & Marinković, 2017), risky sexual behavior (Victor & Hariri, 2016), excessive use of cannabis (Maij, van de Wetering, & Franken, 2017), and alcohol abuse (Nixon, 2013; Silveri, 2012; Weiland et al, 2014). Silveri (2012) argues for postponing the legalization of alcohol consumption until “neurological maturity” in adulthood is reached.…”
Section: The Social Political History Of the Science Of Developmentalmentioning
confidence: 99%
“…One dominant theory about adolescent susceptibility to risky behaviors has been the dual systems model theory which proposes that the emotional centers of youth develop earlier than their more rational cognitive centers (mainly the prefrontal cortex). Therefore, while they experience intense emotions, the theory purports, this is typically not accompanied by mature reasoning thereby predisposing youth to irrational emotions and risk-taking (Knežević & Marinković, 2017; Steinberg et al, 2008; Taber-Thomas & Perez Edgar, 2016). While Steinberg et al (2008), who conceived of the model, offer that this is a simple heuristic technique to explain adolescent behavior, the idea has been expanded and applied to notions of vulnerabilities in EA brains (Wu et al, 2016).…”
Section: The Social Political History Of the Science Of Developmentalmentioning
confidence: 99%
“…ADHD is accompanied by ineffective executive functions such as response inhibition (8). Response inhibition is a key executive function which grows with the onset of puberty which is supported by the frontal lobe (9). It is a neurological element helping children provide delayed responses (10).…”
Section: Introductionmentioning
confidence: 99%